2009
DOI: 10.1103/physrevlett.102.225004
|View full text |Cite
|
Sign up to set email alerts
|

New Features of Electron Phase Space Holes Observed by the THEMIS Mission

Abstract: Observations of electron phase-space holes (EHs) in Earth's plasma sheet by the THEMIS satellites include the first detection of a magnetic perturbation (deltaB_{ parallel}) parallel to the ambient magnetic field (B0). EHs with a detectable deltaB_{ parallel} have several distinguishing features including large electric field amplitudes, a magnetic perturbation perpendicular to B0, high speeds ( approximately 0.3c) along B0, and sizes along B0 of tens of Debye lengths. These EHs have a significant center poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
123
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 93 publications
(142 citation statements)
references
References 29 publications
19
123
0
Order By: Relevance
“…In a previous study based on fully three dimensional PIC simulations we reported electron holes evolving to spherical shape in plasmas with W e > w pe [Singh et al, , 2001a[Singh et al, , 2001b. We have not performed a statistical study, but the sizes and shape found here are comparable to the size and shape of large-amplitude electron holes reported by Andersson et al [2009] and Tao et al [2011]. Tao et al [2011] found that L ?…”
Section: Double Layers In Plasma Sheetsupporting
confidence: 49%
See 3 more Smart Citations
“…In a previous study based on fully three dimensional PIC simulations we reported electron holes evolving to spherical shape in plasmas with W e > w pe [Singh et al, , 2001a[Singh et al, , 2001b. We have not performed a statistical study, but the sizes and shape found here are comparable to the size and shape of large-amplitude electron holes reported by Andersson et al [2009] and Tao et al [2011]. Tao et al [2011] found that L ?…”
Section: Double Layers In Plasma Sheetsupporting
confidence: 49%
“…Although Andersson et al [2009] do not report observation of double layers in association with the electron holes, but Ergun et al [2009] report strong sequential relation between double layers and electron holes, like that shown in Figure 8b. Figure 1a of Andersson et al [2009] shows intense electron fluxes extending to about 30 keV energy range. This is suggestive of double layers having potential drops up to a few tens of kV.…”
Section: Double Layers In Plasma Sheetmentioning
confidence: 83%
See 2 more Smart Citations
“…The expected amplitude range of the DC electric field is based on previous experience. The THEMIS mission observed fields as high as 500 mV/m (Ergun et al 2009;Andersson et al 2009), which provides the basis of the DC range on MMS.…”
Section: Science Requirementsmentioning
confidence: 97%